Sinergi Edukasi dan Aksi dalam Pengabdian Masyarakat: Meningkatkan Kesadaran Pendidikan, Kesehatan, dan Lingkungan di Desa Sukoreno: Synergy of Education and Action in Community Service: Increasing Awareness of Education, Health, and the Environment in Sukoreno Village - Rusdiyanto, Dian; Fadhilah, Dzikri; Sugara, Ujang; Riska, Fati Matur; Supriyatin, Supriyatin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Community service activity programs have been carried out in Sukoreno Village, which include aspects of education, health, and the environment. The activity methods include audiences and observations, seminars and discussions, services and demonstrations, as well as mentoring and evaluation. Community service activities consist of seminars and interactive discussions, practice or demonstration of product making, and health services for the community. In education, the topics presented are motivation for developing potential and delivering materials related to adolescent reproductive health and early marriage. In addition, the handover of the book and bookshelf grants was also given to the Sentolo Satu Health Center. In the health aspect, health checks were carried out for mothers and toddlers, which included anthropometric, hemoglobin, Mantoux examinations, and health consultations. In addition, the provision of materials related to stunting and toddler nutrition was also delivered to the practice of making MPASI using local food ingredients. In the environmental sector, waste management is the main focus, especially the management of organic waste into compost and the creation of biopores. The implementation of community service shows high enthusiasm from the villagers, where discussions on each aspect are attended by many people. This activity requires further assistance to ensure that the understanding of villagers can be implemented. With collaboration from all parties, community service activities in Sukoreno Village are expected to be a breakthrough that is beneficial for residents and improve the quality of life, and can be an example for other community service activities in carrying out real actions.